Muscle adaptations with immobilization and rehabilitation after ankle fracture - Stevens, J. E.; Walter, G. A.; Okereke, E.; Scarborough, M. T.; Esterhai, J. L.; George, S. Z.; Kelley, M. J.; Tillman, S. M.; Gibbs, J. D.; Elliott, M. A.; Frimel, T. N.; Gibbs, C. P.; et al. (Medicine & Science in Sports & Exercise, 2004)
Introduction/Purpose: The widespread occurrence of muscular atrophy during immobilization and its reversal presents an important challenge to rehabilitation medicine. We used 3D-magnetic resonance imaging (MRI) in patients with surgically-stabilized ankle mortise fractures to quantify changes in plantarflexor and dorsiflexor muscle size during immobilization and rehabilitation, as well as to evaluate changes in force generating capacity (specific torque). Methods: Twenty-individuals participated in a 10 wk rehabilitation program after 7 wk of immobilization. MRIs were acquired at baseline, 2, and 7 wk of immobilization, and at 5 and 10 wk of rehabilitation. Isometric plantarflexor muscle strength testing was performed at 0, 5, and 10 wk of rehabilitation. Results: Dorsiflexors and plantarflexors atrophied 18.9% and 24.4% respectively, the majority of which occurred during the first 2 wk of immobilization (dorsiflexors: 9.6%; plantarflexors: 14.1%). Likewise, more than 50% of hypertrophy during rehabilitation occurred within the first 5 wk of rehabilitation for both the dorsiflexors (12.9%) and plantarflexors (13.2%), when compared to the total amount of hypertrophy over 10 wk of rehabilitation (dorsiflexors: 17.6%, plantarflexors: 22.5%). There were no significant differences in hypertrophy or atrophy of the dorsiflexor or plantarflexor muscles, despite a rehabilitation emphasis on the plantarflexors. Patients had significantly lower plantarflexor specific torque (torque/CSA) than healthy, control subjects immediately after cast immobilization, which did not return to normal after 10 wk of rehabilitation (P < 0.05). Conclusion: Our investigation of the consequences of limb immobilization on rehabilitation outcomes in patients can be applied directly to optimizing rehabilitation programs. Although muscle hypertrophy occurred early during rehabilitation, plantarflexor muscle function (specific torque) should remain the focus of rehabilitation programs because although CSA recovered quickly, specific torque still lagged behind that of control subjects.